Colors and Learner’s Gender Evoke Different Emotional and Cognitive Effects in Multimedia Learning - Tze Wei Liew; Su-Mae Tan; Chin Lay Gan; Wei Ming Pang (Human Behavior and Emerging Technologies)
The emotional design principle avers that highly saturated warm colors in multimedia learning presentations can elevate affective-motivational, cognitive, and learning outcomes. While warm and achromatic grayscale color tones have been explored extensively, relatively less research examines the effects of cold colors in multimedia learning. This study explores how color tones (warm, cold, and achromatic grayscale) and learners’ gender influence positive emotions, intrinsic motivation, cognitive load, and transfer performance. An online experiment was conducted where learners pursuing IT courses in an Asian university (n=204) engaged with either one of the multimedia learning lessons on distributed denial-of-service attack imbued with (1) a warm color tone, (2) a cold color tone, and (3) an achromatic grayscale color tone. Findings show that the cold color tone was associated with fewer enhanced positive emotion types than the other color tones. Compared to the achromatic grayscale color tone (M=2.38, SD=1.88), significantly higher extraneous cognitive load ratings were observed with the warm color tone (M=3.26, SD=1.96) and the cold color tone (M=3.24, SD=2.18). Following reports by some learners, this could be attributed to the overly vivid and saturated chromatic colors impairing the learners’ visual and cognitive processes, causing them to rate the multimedia learning experience with warm and cold color tones as more difficult than with the achromatic grayscale color tone. Male learners in the warm color tone condition (M=4.93, SD=3.46) performed marginally better on the transfer posttest than male learners in the cold color tone condition (M=3.49, SD=3.45) and male learners in the achromatic grayscale color tone condition (M=3.44, SD=2.69). In contrast, female learners in the warm color tone condition (M=1.75, SD=1.62) performed marginally worse than female learners in the cold color tone condition (M=3.83, SD=3.92) and significantly worse than female learners in the achromatic grayscale color tone condition (M=3.67, SD=2.50). Overall, these results show that gender can shape the effects of warm colors on learning—the warm color tone can enhance male learners’ but stifle female learners’ transfer performance. Moreover, this study aligns with recent studies that colors as an emotional design feature may lead to higher cognitive load ratings. This paper discusses the theoretical and practical implications and submits a future outlook for broadening the research domain.